Nationwide surveillance for Telmisartan alone or with combination at real world therapy in Indian patients with hypertension (START) - Chopda, Manoj B.; Gadkar, Sunil G.; Lakshmaiah, Yashwanth A.; Lambata, Ravi K.; Dabhade, Dhammadeep C.; Newale, Sanket R. (International Journal of Research in Medical Sciences, 2021)
Background: Angiotensin receptor blockers (ARBs) are amongst the most preferred class of antihypertensive as reported at various evidences or guidelines. However, choice amongst ARBs differs between practicing physicians in real-life scenario. This survey aimed to understand the usage preferences of telmisartan therapy alone and in combination for treating hypertension (HT) among practitioners at various clinical settings in real-life scenario in India. Methods: A cross‑sectional survey was conducted with a pre-validated survey questionnaire consisting of 15 questions pertaining to the telmisartan and its combination usage in HT management. Total 498 registered medical practitioners (mostly physicians and cardiologists) had participated in survey. They were approached for seeking their perception, opinions, and prescribing behaviour. Categorical data was summarized by number (n) and percentage (%) in each category. Data were summarised in frequency tables. Results: Key findings from the data analysed were as follows: Around 20-40% of patients been reported to have co-morbid hypertension and diabetes as reported by majority of the physicians. Preferred class of drug in patients with hypertension with diabetes reported to be ARB. Around 90.36% of doctors reported that telmisartan was the most preferred ARB in patients with hypertension associated with high cardiovascular risk. Around 90.76% of doctors reported for their preference for telmisartan in patients with hypertension for 24-hr BP control. Around 82.93% of doctors preferred telmisartan in patients with hypertension and stroke/post-MI status. Conclusions: Indian healthcare practitioners prefer telmisartan as the most preferred ARB either alone or in a combination in patients with hypertension, including those with comorbidities.